A atuação do psicólogo no contexto das referências ambulatoriais em saúde mental de Aracaju - SE - Guimarães, Shyrley Bispo (2011)
Psychologists‟ insertion in mental healthcare ambulatory clinics occurred during the decade of 1980, in the context of the claims disseminated by sanitary and psychiatric reforms, of the formation of minimum mental healthcare teams and of the retraction of the private clinic. Historically, this migration had been accompanied by the importation of practices traditionally applied at the clinics. Furthermore, the lack of clear guidelines from the Health Ministery occasioned the opening of ambulatory clinics with diversified structures at each city. The objective of this dissertation was to study the practices of psychologists at mental healthcare ambulatory references at Aracaju-SE. Were interviewed psychologists of these services and managers of the municipal health secretary using a semi-structured interview guideline, in addition to the analysis of management reports. It was observed that the mental healthcare references had experienced substantial changes referred to its structures and operation, leading to a present framework of expansion and readjustment. It was realized that there is an effort by the psychologists to maintain individual and group assistance, using adjustments in the frequency of the sessions and in the focus of the activities. Besides the progresses, the relation with the psychiatrist still works basically through the medical record, blocking advances on joint discussions of the cases. Some advances toward the amplified clinic are notable, like the overcoming of the isolated usage of psychiatric diagnostic and the replacement of the line‟ criterion by the urgency one. Sheltering had become an interesting strategy on flux ordination, however the mismatch between offer and demand seems to be a matter which extrapolates the psychologists‟ sphere at the references. For this reason the narrow of the relation with family healthcare centers seems to be the major challenge to be faced by psychologists at mental healthcare ambulatory references